A Concave Security Market Line - Enrico G. De Giorgi; Thierry Post; Atakan Yalcin (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
We provide theoretical and empirical arguments in favor of a concave shape for the security market line, or a diminishing marginal premium for market risk. In capital market equilibrium with binding portfolio restrictions, different investors generally hold different sets of risky securities. Despite the differences in composition, the optimal portfolios generally share a joint exposure to systematic risk. Equilibrium in this case can be approximated by a concave relation between expected return and market beta rather than the traditional linear relation. An empirical analysis of U.S. stock market data confirms the existence of a significant and robust, concave cross-sectional relation between average return and estimated past market beta. We estimate that the market-risk premium is at least five to six percent per annum for the average stock, substantially higher than conventional estimates.
Keywords: G12; C21; 330; capital market equilibrium; asset pricing; investment restrictions; portfolio theory; Wertpapierhandel; Anlageverhalten; Risikoprämie; Portfolio-Management; USA